Wavelet coherence phase analysis decodes the universal switching mechanism of Ras GTPase superfamily - Motiwala, Zenia; Sandholu, Anand S.; Sengupta, Durba; Kulkarni, Kiran (iScience, 2023)
The Ras superfamily of GTPases regulate critical cellular processes by shuttling between GTP-bound ON and GDP-bound OFF states. This switching mechanism is attributed to the conformational changes in two loops, SWI and SWII, upon GTP binding and hydrolysis. Since these conformational changes vary across the Ras superfamily, there is no generic parameter to define their functional states. A unique wavelet coherence (WC) analysis-based approach developed here shows that the structural changes in switch regions could be mapped onto the wavelet coherence phase couplings (WPCs). Thus, WPCs could serve as unique parameters to define their functional states. Disentanglement of WPCs in oncogenic GTPases shows how breakdown of structural allostery leads to their aberrant function. These observations stand out even for simulated ensemble of switch region conformers. Overall, for the first time, we show that WPCs could unravel the latent structural deviations in Ras proteins to decode their universal switching mechanism.